Caracterização morfológica dos pequenos mamíferos não voadores da estação ecológica Santa Bárbara, SP: Um fragmento de cerrado no sudeste do Brasil - Felicio, Giovana Ribeiro (Universidade Federal de São Carlos, 2023)
The Cerrado is characterized by a mosaic of vegetation, this diversity of habitats, in turn, is responsible for the vast wealth of small mammals present in the domain, which includes both species associated with forest formations and those specialized in open areas. Given that the Santa Bárbara Ecological Station, in the state of São Paulo, is one of the few conservation units located in the south of the domain that still preserves this mosaic of physiognomies, it represents a key area for the conservation and understanding of the biogeography of these mammals and of the Cerrado. In this context, the objective of this study was to morphologically characterize and taxonomically identify the marsupials and rodents of this region, contributing to increasing knowledge regarding the occurrence, geographic distribution and morphological variation of this group in the southern portion of the Cerrado. The analyzed material is preserved in the Mammal Systematics Laboratory at UFSCar, Sorocaba campus. The specimens were classified according to sex and age class and examined for qualitative and quantitative external morphology and craniodental characteristics. Qualitative and quantitative data were obtained and expressed in the form of comparative tables, generating standard statistical data (mean, maximum and minimum values, standard deviation) of the variables analyzed for each species. Between 2017 and 2021, monthly expeditions were carried out to sample mammals, using capture traps in the “Sherman”, “Tomahawk”, Cage and “Pitfall” models. 247 specimens were collected, distributed across 17 native species, 11 species belonging to the Order Rodentia and 6 to the Order Didelphimorphia, with 135 adult individuals included in the morphometric analyses, of which 29 are marsupials and 106 rodents. The results reveal a high richness for the study area, and confirm the occurrence of the species Cerradomys scotti, expanding the record of occurrence of the species to the state of São Paulo, as well as for G. agilis, Monodelphis kunsi, Hylaeamys megacephalus, Oligoryzomys mattogrossae , Oxymycterus delator, Rhipidomys macrurus and Clyomys laticeps, which have few records in the state, restricted to its northern and/or western portion. Unpublished data for the state were represented by records of Cryptonanus chacoensis and Cryptonanus aff. chacoensis. These results contribute to increasing knowledge and the conservation of small non-flying mammals in this southern portion of the Cerrado, which stands out for being still little known, highly fragmented and represented by few conservation units.
Morphological characterization of small non-flying mammals from Santa Bárbara, SP ecological station: A fragment of cerrado in southeastern Brazil
Keywords: Conservação; Marsupiais; Morfologia; Roedores; Taxonomia; Estação Ecológica Santa Bárbara; Conservation; Marsupials; Morphology; Rodents; Taxonomy; Santa Bárbara Ecological Station; CIENCIAS BIOLOGICAS::MORFOLOGIA; CIENCIAS BIOLOGICAS::ZOOLOGIA; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES